Framing physical literacy through a rehabilitation lens: A health promotion role for physiotherapists - Petrusevski, Celeste (My University, 2022)
Increasing access to and improving knowledge of rehabilitation strategies is essential to address the adverse health outcomes related to the increased prevalence of multimorbidity with our aging population. Physical literacy is emerging as a strategy to increase lifelong participation in physical activity, however, there is limited research exploring how physical literacy can support optimal aging for adults with functional decline associated with chronic conditions. This thesis investigated how to frame physical literacy for adults through a rehabilitation lens and explored outcomes related to function, mobility, and health awareness as a result of a novel physical literacy intervention. The first study was an integrative review examining what is known about physical literacy for adults. Thirteen new physical literacy constructs emerged, that differed from the current physical literacy definition and addressed the needs of aging adults. Purposeful activities, knowledge of age-related changes, and social interaction were identified as the top three. The objective of the second expert consensus study was to understand what components are required when acquiring physical literacy as an adult from the perspectives of healthcare professionals and researchers in optimal aging. The third qualitative study explored how adults with multimorbidity describe physical literacy for adults while considering barriers and facilitators associated with fluctuating health status. The findings from the preceding qualitative studies helped inform the program development of the fourth physical literacy intervention study and fostered a new rehabilitation-focused Physical Literacy framework for Adults and adults with Chronic Conditions (PLACC). A pre-post study involving 20 adults with 2 or more conditions (95% female, 59 + 6 years) participated in a 5-week multi-component, virtually delivered physical literacy group intervention. Post-intervention significant improvements were found for physical function (p=<0.001; cohen’s D=0.90), as measured by the patient specific functional scale, mobility with the 4-meter walk test at self-selected speed (p=0.03, cohen’s D=0.53) and all 3 physical literacy awareness questions (p=0.001, p=<0.001, p=0.001). The results of this program of research can inform future public health interventions, involving rehabilitation-focused physical literacy programs, designed by physiotherapists, and aimed at improving function and mobility for adults with chronic conditions.
Keywords: physical literacy; multimorbidity; older adults; physiotherapy